2014
DOI: 10.3906/vet-1405-101
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the efficacy of Tarantula cubensis extract (Theranekron D6) in the treatment of subclinical and clinical mastitis in dairy cows

Abstract: IntroductionDefined as inflammation of the mammary gland, mastitis is the most common disease of dairy cattle, and it causes major economic losses (1). The disease reduces milk yield, alters milk composition, and shortens the productive life of affected dairy cattle. Seventy to eighty percent of milk losses caused by mastitis arise from subclinical cases (2). The changes observed in the composition of milk in subclinical mastitis include the presence of plasma proteins, alterations in ion concentrations, the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Spider venoms are known to have an anticancer perspective, via tempering the cell cycle, several cell death mechanisms, ion channels and receptors [22]. T. cubensis alcoholic extract, commercially named Theranekron ® , is commonly used as a veterinary remedy [23]. It is known to have several therapeutic effects such as anti-inflammatory, antitumor and wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…Spider venoms are known to have an anticancer perspective, via tempering the cell cycle, several cell death mechanisms, ion channels and receptors [22]. T. cubensis alcoholic extract, commercially named Theranekron ® , is commonly used as a veterinary remedy [23]. It is known to have several therapeutic effects such as anti-inflammatory, antitumor and wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…Althought some literatures were reported that, TC has been found an effective agent on the treatments of some animal diseases we have not seen any positive effect on liver regeneration, and also same situation may have say for MS. But, in the future (at different dose and durations) these may be found effective [2][3][4][5][6][7][8].…”
Section: İnfiltrationmentioning
confidence: 99%
“…It is used in veterinary medicine in cases of septic conditions, such as dermatitis, inflammatory nail diseases (panaricium, foot rot), phlegumones, ulcers, abscesses, purulent lesions and necrosis. It is stated that it can be accelerate uterus involution and reduce vaginal discharge in the early postpartum period, and also it may be used as an alternative therapeutic for the treatment of clinical and subclinical mastitis in dairy cattle [2][3][4]. Additionally, in blue tongue infections of cattle, administration of TC together with oxytetracycline and flunixin have shown fever returns to normal earlier and re-epithelization accelerates, and it is more effective than alone levamisole administration in the treatment of nipple papillomatosis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Theranekronis used in the treatment of many genital diseases such as mastitis, breast edema, retention of secundinarium, papillomatosis, breast tumor, genital organ tumors, metritis (Kaçar et al, 2007;Oryan et al, 2012;Swamy et al, 2020;Sardari et al, 2007;Ghasemi et al, 2016;Lotfollahzadeh, 2020;Gürbulak et al, 2014;Stampa, 1986;Icen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%